Remote assessment of platelet function in patients with acute stroke or transient ischaemic attack - Bath, Philip M.W.; May, Jane; Flaherty, Katie; Woodhouse, Lisa J.; Dovlatova, Natalia; Fox, Sue C.; England, Timothy J.; Krishnan, Kailash; Robinson, Thompson G.; Sprigg, Nikola; Heptinstall, Stan (Hindawi, 2017)
Background: Antiplatelets reduce recurrence after cerebral ischaemia. The international TARDIS trial assessed the safety and efficacy of intensive (combined aspirin, dipyridamole and clopidogrel) versus guideline (aspirin and dipyridamole, or clopidogrel alone) antiplatelet agents given for one month in patients with acute stroke or TIA. The aim of this substudy was to assess the effect of antiplatelet agents taken at baseline on platelet function reactivity and activation. Methods: In a substudy, platelet function, assessed by remotely measured surface expression of P-selectin (CD62P, Platelet Solutions Ltd), was assessed at baseline in patients who were and were not taking antiplatelet agents at the time of randomisation. Data are Median Fluorescence values (MF). Results: The aspirin P-selectin test demonstrated that platelet expression was lower in 485 patients taking aspirin than in 171 patients taking no aspirin: mean 209 (SD 188) vs. 552 (431), difference 343 (95% confidence intervals, CI 295.3, 390.7) (2p<0.001). Aspirin did not suppress P-selectin levels below 500 units in 22 (4.5%) patients. The clopidogrel P-selectin test showed that platelet reactivity was lower in 96 patients taking clopidogrel than in 586 patients taking no clopidogrel: 653 (297) vs. 969 (315), difference 316.1 (95% CI 248.6, 383.6) (2p<0.001). However, clopidogrel did not suppress P selectin level below 860 units in 24 (24.7%) patients. Conclusions: Aspirin and clopidogrel each suppress stimulated platelet P-selectin although one quarter of patients on clopidogrel have high on-treatment platelet reactivity. Platelet function testing, assessed as platelet P-selectin expression, may be performed remotely in the context of a large multicentre trial.